PENDIDIKAN KEAGAMAAN DI LINGKUNGAN KELUARGA DAN SEKOLAH DALAM MENANAMKAN NILAI NILAI AKIDAH AKHLAQ PADA SISWA DI MADRASAH TSANAWIYAH NEGERI 1 SUKOHARJO TAHUN AJARAN 2025-2026 - Humairoh Adinda Kurniawati (STKIP Pesisir Selatan, 2026)
This study aims to analyze the role of religious education within the family and school environments in instilling Islamic creed and moral values among students at Madrasah Tsanawiyah Negeri 1 Sukoharjo and to identify the supporting and inhibiting factors in the digital era. This research employed a qualitative approach using a case study design. Informants were selected through purposive sampling, involving Islamic Religious Education teachers, seventh-grade students, and parents. Data were collected through interviews, observations, and documentation. Data analysis applied the Miles and Huberman model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that religious education within the family is implemented through habituation of worship, parental role modeling, advice, and behavioral supervision. In the school environment, the inculcation of Islamic creed and moral values is carried out through Akidah Akhlak learning, teacher exemplification, and religious activities such as congregational prayers and Qur’anic recitation.